Microalgae diversity in varying habitat characteristics in Pasuruan and Sidoarjo coastal areas, East Java, Indonesia - MOHAMMAD MAHMUDI; SULASTRI ARSAD; FIKA FITRIANESIA; SAFRIZAL FIKRI RAMADHAN; ABDUR RAHMAN ARIF; FRIZCA RANIA SAVITRI; ADELITA ASMO DEWINTA; ANINDYA DIVANATA ONGKOSONGO; MUHAMMAD MUSA; EVELLIN DEWI LUSIANA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Mahmudi M, Arsad S, Fitrianesia F, Ramadhan SF, Arif AR, Savitri FR, Dewinta AA, Ongkosongo AD, Musa M, Lusiana ED. 2023. Microalgae diversity in varying habitat characteristics in Pasuruan and Sidoarjo coastal areas, East Java, Indonesia. Biodiversitas 24: 4418-4426. Microalgae are microscopic eukaryotic organisms which live in various types of habitats. The purpose of this study was to identify the types and the abundance of microalgae in several sub-habitats, namely sediments, mangroves, water columns, and artificial substrates; and to analyze the environmental factors that affect the abundance of microalgae. The research was conducted in several sites in the coastal areas in Pasuruan and Sidoarjo, East Java, Indonesia. A quantitative descriptive method was applied with data collection used a purposive sampling method. Samples were collected using net for planktonic microalgae and using sampling plot for epiphytic and benthic microalgae. The microalgae were grouped using NMDS (non-metric multidimensional scaling) and the relationships between microalgae abundance and water quality parameters were analyzed using CCA (canonical correspondence analysis). The results show that Bacillariophyceae, Cyanophyceae, and Chlorophyceae classes were found in all study sites, but Trebouxiophyceae and Dinophyceae were only found in Pasuruan Beach. The highest abundance of microalgae was found in sediment habitat in Wughoyo Beach, Sidoarjo with 706,605 ind. cm-2. The diversity, the evenness, and the dominance index in both coastal areas ranged from 1.43-2.61; 0.71-0.96; and 0.06-0.27, respectively. Similarity analysis using the NMDS showed that there was no similarity among the three sites, suggesting each site had high microalgal variation. The CCA analysis showed that Bacillariophyceae were found in all sites, indicating its high adaptability. The results of this analysis imply that particular habitat has a unique microalgae diversity, thus preserving diverse habitat types is important.